2019
DOI: 10.1002/jsfa.9610
|View full text |Cite
|
Sign up to set email alerts
|

Consuming egg yolk decreases body weight and increases serum HDL and brain expression of TrkB in male SD rats

Abstract: BACKGROUND Egg yolks contain large amounts of cholesterol and are suspected to be harmful after long‐term consumption. In this experiment, 63 rats were used to evaluate the effect of egg white (EW) and egg yolk (EY) supplementation on serum lipids and brain cognition. The feeding time lasted 4 weeks after a 1‐week acclimation. RESULTS Body weight was significantly higher in rats fed 132.0 g kg−1 EW and significantly lower when fed 40 g kg−1 EY (P < 0.05). Total cholesterol and low‐density lipoprotein increased… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

1
10
0

Year Published

2020
2020
2024
2024

Publication Types

Select...
7

Relationship

0
7

Authors

Journals

citations
Cited by 14 publications
(13 citation statements)
references
References 34 publications
1
10
0
Order By: Relevance
“…The expressive upregulation (approximately 40%) of the TrkB receptor observed in hippocampi may reflect an adaptive compensatory response to diet‐induced downregulation of BDNF, similar to previous outcomes about stress (Nibuya et al, 1999). Taken that decreased BDNF has been related to eating behavior and energy expenditure (Chen et al, 2019; Marosi & Mattson, 2014; Noble et al., 2011), we can suggest a central role of brain BDNF in eating behavior impairments here observed. In accordance, hypothalamic infusions with BDNF can impact eating behavior and reduce overweight in mutant mice (Kernie et al.…”
Section: Discussionsupporting
confidence: 69%
See 1 more Smart Citation
“…The expressive upregulation (approximately 40%) of the TrkB receptor observed in hippocampi may reflect an adaptive compensatory response to diet‐induced downregulation of BDNF, similar to previous outcomes about stress (Nibuya et al, 1999). Taken that decreased BDNF has been related to eating behavior and energy expenditure (Chen et al, 2019; Marosi & Mattson, 2014; Noble et al., 2011), we can suggest a central role of brain BDNF in eating behavior impairments here observed. In accordance, hypothalamic infusions with BDNF can impact eating behavior and reduce overweight in mutant mice (Kernie et al.…”
Section: Discussionsupporting
confidence: 69%
“…Considering gestational exposure to HDs may alter hippocampal BDNF levels even in postnatal day (PND) 21, an usual time point for weaning (Richter et al, 2016), the relationship of central BDNF and framework of feeding pattern can bring clues about eating behavior changes induced by HD. In addition, taken that BDNF selectively activates tyrosine kinase receptor (TrkB), BDNF and TrkB can be evaluated in order to elucidate the BDNF function (Chen et al, 2019; Noble et al, 2011).…”
Section: Introductionmentioning
confidence: 99%
“…We previously demonstrated that WE consumption for 8 wk is effective at improving serum vitamin D status and providing nephroprotective benefits [ 17 , 18 ]; however, despite our gene expression findings in this study we still have yet to elucidate the mechanism underlying how WE consumption leads to decreased weight gain [ 28 , 29 ]. We also identified that ZDF rats fed WE upregulated 11 genes involved in glutathione metabolism in the liver and kidney.…”
Section: Resultsmentioning
confidence: 90%
“…Several research explained that the consumption of carotene and zeaxanthin derived from corn caused an increase in the expression of several genes. 15,16 The downstream effects that arise consist of changes in weight, energy and fat metabolism, regulation of apoptosis, and tumor suppression. In addition, consumption of these two active compounds also causes a decrease in gene expression of enzymes responsible for oxidative Table 6.…”
Section: Body Weight Changes and General Observationsmentioning
confidence: 99%